A case report of laparoscopic cholecystectomy of acute gangrenous cholecystitis with hypoplasia of medial segment of the liver and Chilaiditi syndrome - NAKASHIMA, Ken; KAWANO, Michikazu; IBUSUKI, Kazuhiko; UCHI, Shoji TANIG; KOGA, Kazumi; MUTO, Mitsuru; GOTOH, Takashi; SEKI, Takashi; YAMAMOTO, Atsushi; MUKAI, Motoi (Tando, 2005)
A 70-year-old man was admitted to our hospital for liver dysfunction and acute cholecystitis. Abdominal X-ray and computed tomography revealed wall thickness of the gallbladder and hypoplasia of medial segment of the liver associated with Chilaiditi syndrome. In order to improve the patient-condition, PTGBD was performed at the back of the patient via intercostal approach, because of his anatomical location of the gallbladder. After four days of antibiotics-prescribing, laparoscopic cholecystectomy was successfully performed by choosing the adequated site of working ports.